Bacterial rhomboid proteases mediate quality control of orphan membrane proteins. (27th April 2020) - Liu, Guangyu; Beaton, Stephen E; Grieve, Adam G; Evans, Rhiannon; Rogers, Miranda; Strisovsky, Kvido; Armstrong, Fraser A; Freeman, Matthew; Exley, Rachel M; Tang, Christoph M
Abstract: Although multiprotein membrane complexes play crucial roles in bacterial physiology and virulence, the mechanisms governing their quality control remain incompletely understood. In particular, it is not known how unincorporated, orphan components of protein complexes are recognised and eliminated from membranes. Rhomboids, the most widespread and largest superfamily of intramembrane proteases, are known to play key roles in eukaryotes. In contrast, the function of prokaryotic rhomboids has remained enigmatic. Here, we show that the Shigella sonnei rhomboid proteases GlpG and the newly identified Rhom7 are involved in membrane protein quality control by specifically targeting components of respiratory complexes, with the metastable transmembrane domains (TMDs) of rhomboid substrates protected when they are incorporated into a functional complex. Initial cleavage by GlpG or Rhom7 allows subsequent degradation of the orphan substrate. Given the occurrence of this strategy in an evolutionary ancient organism and the presence of rhomboids in all domains of life, it is likely that this form of quality control also mediates critical events in eukaryotes and protects cells from the damaging effects of orphan proteins. Synopsis: Comprehensive identification of bacterial rhomboid intramembrane protease substrates reveals a quality control function in removal of unincorporated subunits of multi‐membrane‐protein complexes. Shigella sonnei encodes two rhomboid proteases, GlpG and previously uncharacterised Rhom7. Shigella rhomboids selectively cleave orphan components of hydrogenase‐2 and formate dehydrogenases. Cleavage by rhomboid proteases is necessary for further degradation of orphan protein substrates. Orphan protein substrates not processed by rhomboid proteases accumulate in the inner membrane and form aggregates. Abstract : Initial cleavage by Shigella sonnei intramembrane protease is a prerequisite for further degradation of orphan multi‐membrane‐protein complex subunits and prevention of their aggregation.